Peran Mediasi Customer Satisfaction Pada Pengaruh Service Convenience Dan Religious Motive Terhadap Word Of Mouth Nasabah Bank Syari’ah - Adhan Hukama (ITB AAS INDONESIA Surakarta, 2023)
This research focuses on studying how service convenience and religious motives influence word of mouth and whether customer satisfaction mediates service convenience and religious motives on word of mouth of Syari'ah Bank customers in DKI Jakarta and West Java. A total of 119 respondents were involved in this research. In this research, the data analysis method used is Structural Equation Modeling-Partial Least Squares (SEM-PLS). This research revealed religious motives and service convenience on customer satisfaction. Apart from that, religious motives influence word of mouth. Meanwhile, service convenience has no effect on customer satisfaction. The results of mediation testing in this research show that customer satisfaction is proven to be able to mediate the influence of service convenience and religious motives on word of mouth of Syari'ah Bank customers.